Nominally brittle cracks in inhomogeneous solids: from microstructural disorder to continuum-level scale - Barés, Jonathan; Barlet, Marina; Rountree, Cindy L.; Barbier, Luc; Bonamy, Daniel (Frontiers in Physics, 2014)
We analyze the intermittent dynamics of cracks in heterogeneous brittle materials and the roughness of the resulting fracture surfaces by investigating theoretically and numerically crack propagation in an elastic solid of spatially-distributed toughness. The crack motion split up into discrete jumps, avalanches, displaying scale-free statistical features characterized by universal exponents. Conversely, the ranges of scales are non-universal and the mean avalanche size and duration depend on the loading microstructure and specimen parameters according to scaling laws which are uncovered. The crack surfaces are found to be logarithmically rough. Their selection by the fracture parameters is formulated in term of scaling laws on the structure functions measured on one-dimensional roughness profiles taken parallel and perpendicular to the direction of crack growth.